Gelfoam slurry tract occlusion after computed tomography‐guided percutaneous lung biopsy: Does it prevent major pneumothorax?. Issue 6 (13th June 2021) - Sum, Reuben; Lau, Theodore; Paul, Eldho; Lau, Kenneth
Abstract: Introduction: Computed tomography (CT)‐guided lung biopsy is a frequently performed procedure in the diagnostic workup for suspicious lung nodules that can be complicated by pneumothorax. This retrospective study assessed the efficacy of biopsy tract occlusion with a gelatin sponge slurry for preventing post‐biopsy pneumothorax. Methods: Retrospective analysis was conducted on consecutive adult patients who underwent CT‐guided lung biopsy over a 10‐year period. Age, gender, existing chronic obstructive pulmonary disease (COPD), evidence of emphysema on CT, location of the lesion and the presence of pneumothorax on post‐procedure CT and 4‐h chest radiograph were recorded. Results: Two hundred and ninety‐six patients were included (126 patients in the non‐gelfoam group and 170 in the gelfoam group). When gelfoam was used, risk of developing an immediate pneumothorax was lower ( P = 0.032). Patients with emphysema were 2.4 times more likely to develop a delayed pneumothorax without gelfoam ( P = 0.034). There was a significantly higher risk of both immediate and delayed pneumothorax in non‐peripheral lesions without gelfoam ( P = 0.001 and P = 0.002, respectively). The frequency of requiring a chest tube to treat a pneumothorax was 86% lower when gelfoam was used ( P = 0.012). Conclusion: Gelfoam is effective in preventing immediate pneumothorax. In patients with emphysema, there was a significantly higher risk of delayed pneumothorax without gelfoam. Additionally, non‐peripheral lesions were more likely to develop pneumothorax when gelfoam was not used. The use of gelfoam was especially important in preventing the development of major pneumothoraces that would require drainage with a chest tube.